The South China Sea dispute: A comparison between the approaches of Presidents Aquino III and Duterte of the Philippines / Rohayu Rahman - Rohayu , Rahman (2019)
Disputes among several claimants over the South China Sea are often illustrated as a controversial issue that affects Southeast Asian region’s stability. The change in the presidency of the Philippines has influenced the foreign policy approaches taken by the Philippines in their relations with China. The objective of this research is to investigate the South China Sea dispute between China and the Philippines especially under Aquino III (2010-2016) and Duterte (2016-present) by examining their different approaches in the dispute. As proven from this study, it is remarkable that Aquino III’s approach in managing the South China Sea dispute was aggressive and he had made more attempts to counter China’s aggression than to contain China. In contrast, during the Duterte’s Presidency, his approach to manage the South China Sea with China has been significantly different than his predecessor and has caused relations between the Philippines and China to dramatically improve. These different approaches taken by both Aquino III and Duterte hence, have played an important role in shaping their foreign policy with China. This research covers the period between the years 2010 to 2018, and the neo-classical realism theory is used as a framework to understand and explain the different approaches adopted by Aquino III and Duterte in managing the South China Sea dispute.